The event of encounter in art and philosophy : continental perspectives - Korhonen, Kuisma, 1964-; Räsänen, Pajari, 1968-; Gaudeamus oy (Helsinki : Gaudeamus Helsinki University Press, 2010)
The event of encounter in art and philosophy / Kuisma Korhonen & Pajari Räsänen -- Amor de lonh - on textual encounters / Kuisma Korhonen -- On the structure of the scenic encounter / Esa Kirkkopelto -- Robbe-Grillet's ethics of non-narrativity in the post-war context (Sartre, Levinas, Barthes) / Hanna Meretoja -- 'Undecidably equivocal': on 'Todtnauberg' and forgiveness / Pajari Räsänen -- From perception to fascination, from representation to image: total encounter in Maurice Blanchot / Outi Alanko-Kahiluoto -- Fascinations: some thoughts after ' From perception to fascination, from representation to image' / Pajari Räsänen -- Encounters: affect, individuation, and territory in Deleuze & Guattari / Janne Vanhanen -- Partage - On the structure of encounter after Nancy and Rancière / Heikki Kujansivu -- Meeting with oneself: the work of art as portrait in Jean-Luc Nancy's Philosophy of art / Martta Heikkilä.
The event of encounter in art and philosophy / Kuisma Korhonen & Pajari Räsänen -- Amor de lonh - on textual encounters / Kuisma Korhonen -- On the structure of the scenic encounter / Esa Kirkkopelto -- Robbe-Grillet's ethics of non-narrativity in the post-war context (Sartre, Levinas, Barthes) / Hanna Meretoja -- 'Undecidably equivocal': on 'Todtnauberg' and forgiveness / Pajari Räsänen -- From perception to fascination, from representation to image: total encounter in Maurice Blanchot / Outi Alanko-Kahiluoto -- Fascinations: some thoughts after ' From perception to fascination, from representation to image' / Pajari Räsänen -- Encounters: affect, individuation, and territory in Deleuze & Guattari / Janne Vanhanen -- Partage - On the structure of encounter after Nancy and Rancière / Heikki Kujansivu -- Meeting with oneself: the work of art as portrait in Jean-Luc Nancy's Philosophy of art / Martta Heikkilä.
931756
Keywords: Robbe-Grillet, Alain; Celan, Paul; Heidegger, Martin, -- 1889-1976.; Blanchot, Maurice; Deleuze, Gilles; Guattari, Félix.; Nancy, Jean-Luc.; Rancière, Jacques; 1100-luku; 1100-talet; kohtaaminen; filosofia; taidefilosofia; taide; kirjallisuus; teatteritaide; esittävät taiteet; hermeneutiikka; trubaduurit (keskiaika); esitykset; kaipaus; kerronta; uusi romaani; representaatio; identiteetti; itse; trubaduurit; hermeneutik; trubadurer (medeltiden); mötande; filosofi; konstfilosofi; konst; litteratur; teaterkonst; scenisk konst; föreställningar (framföranden); längtan; berättande; nya romanen; representation (framställning); identitet (självbild); självet; trubadurer; kirjallisuudentutkimus; lyriikka -- tulkinta; uusi romaani -- Ranska; Ranska; Frankrike; sammanträffande